Comparison of arthroscopic debridement and microfracture in the treatment of osteochondral lesion of talus - Zhang, Minghua; Chen, Daohua; Wang, Qiang; Li, Ying; Huang, Shiming; Zhan, Peng; Lai, Jiajing; Jiang, Jianqing; Chen, Dongfeng (Frontiers in Surgery, 2023)
Objective This study was performed to compare the clinical effect of arthroscopic debridement vs. arthroscopic microfracture in the treatment of osteochondral lesions of the talus. Methods We retrospectively reviewed patients with osteochondral lesion of talus who were admitted to our hospital from April 2020 to April 2021. The patients were divided into Group A (arthroscopic debridement group, n = 39) and Group B (arthroscopic microfracture group, n = 42), and the intraoperative details in the two groups were analyzed. The American Orthopaedic Foot and Ankle Society (AOFAS) score and visual analogue scale (VAS) score were compared between the two groups before surgery and at the last follow-up. Results The postoperative AOFAS score (Group A, 40.9–82.26; Group B, 38.12–87.38), VAS score (Group A, 6.44–3.92; Group B, 6.38–2.05) significantly improved in both groups, but the improvement was significantly greater in Group B than in Group A (P < 0.05). Among all patients, the AOFAS and VAS scores of men aged ≤30 years and patients with a low body mass index (BMI) improved more significantly (P < 0.05). Conclusion The arthroscopic microfracture for the treatment of osteochondral lesion of talus is superior to joint debridement in terms of improving ankle function, especially in relatively young men with a relatively low BMI.